Attack of the bandit cats - Stilton, Geronimo (New Delhi Scholastic, 2024)
From the massively demanded and applauded series of Geronimo Stilton comes the eighth book Attack of The Bandit Cats: 08 (Geronimo Stilton #08), by Elisabetta Dami. The book is a rich fictional novel for the children due to its talking mouse characters, a gripping storyline and unexpected chilling turns. Every mouse is panicked by the footsteps of a cat and being trapped in a ship full of cats would be a mouse's biggest nightmare.Geronimo published a phone-book with the phone numbers of the residents of New Mouse's city and it gets disastrously late before he realizes that all phone numbers were printed wrong. As the books were sold and Geronimo had to hide from every single complaining customer. His cousin, Trap Stilton, offers Geronimo to join on a quest to a legendary island, which is known for its silver treasures hidden in it. Running from one place, Geronimo finds himself in another problem as soon as this mob of mice is captured by pirate cats. This mice-group is helpless and has to cook food for the cats, where they are going to be the key ingredient of the cat-food. The run for life and the plans Geronimo make keep the readers glued to the book till the end.The nerve-chilling plot, unpredictable chapters and the artistic narration of the whole journey from the mouse-hero itself, makes this book a great reading experience for the children. Attack of The Bandit Cats: 08 (Geronimo Stilton #08) was published in paperback by Scholastic Incorporated as 1st edition in 2004. Key Features: After being highly successful in Italian version, this series of books was published in English. The series was titled as best seller and Award Winning Children's Titles.